Financial Conflicts of Interest Among Oncologist Authors of Reports of Clinical Drug Trials - Wayant, Cole (JAMA Oncol, 2018)
This analysis investigates the prevalence of financial relationships between oncologist authors of clinical drug trials and the pharmaceutical industry and how often such financial interests are unreported.